Market transparency and competition policy - H. Peter Møllgaard; Per Baltzer Overgaard (Copenhagen Business School (CBS), Department of Economics, 2001)
We survey some of the literature on the effects of improved market transparency on competition in ologopoly. Generally, improved transparency from the perspective of irms makes detection of deviations from tacitly collusive agreements easier, thus facilitating oligopolistic coordination. On the other hand, improved transparency from the perspective of consumers, particularly in terms of easier comparability of goods characteristics, has ambiguous effects: More elastic demands make deviations from collusive prices more profitable to firms in the short run, but they also make future retaliation by rivals more severe. Which of these forces will dominate in a dynamic oligopoly competition is shown to depend on the market-specifics. In light of the theoretical results, we discuss the likely effects on inter-firm competition of information exchange and online trading institutions as well as the American and European competition policy attitude towards market transparency.
hdl:10398/7567
Keywords: D18; D43; L13; L41; 330; Market transparency; Repeated oligopoly; Secret price-cutting; Customer switching